A Cost-Effective Electrical Stimulation Device for Non-Pharmacological Pain Management During Pregnancy - Muhammad Omar Cheema; Zia Mohy Ud Din; Jahan Zeb Gul; Fawad Salam Khan; Mohd Norzali Haji Mohd; David Lim (International Journal of Integrated Engineering, 2026)
Pain related to pregnancy is due to the physical changes that occur in a woman’s body to accommodate the growing fetus. Pain management during pregnancy requires a balance between effective relief and the safety of the mother. Presently, pain management includes medication and therapy methods. Non-pharmacological methods should be prioritized over pharmacological methods to relieve the pain due to the adverse side effects of medication on both the mother and the fetus. In this study, a novel electrical stimulation device is designed and developed for non-pharmacological pain management during pregnancy. The device provides biphasic electrical pulses noninvasively using electrode pads. The device can be used by both pregnant females and females suffering from period cramps. The designed and developed device is cost-effective, portable, and modular. In the future, the device can be made smart by controlling it via the mobile application using wireless communication. It can also be integrated into therapeutic systems for maternal care.